Mode I fracture growth in anisotropic rocks: Theory and experiment. (15th June 2020) - Nejati, Morteza; Aminzadeh, Ali; Amann, Florian; Saar, Martin O.; Driesner, Thomas
Highlights: Mode I cracks in anisotropic rocks tend to kink towards foliation/bedding planes. Experiment data are compared to the predictions of different growth criteria. Maximum tangential stress criterion predictions are closest to the experiment data. The inclusion of the T-stress improves the predictions of the growth criteria. Abstract: This paper presents the results of 124 pure Mode I fracture toughness tests on two types of anisotropic rocks, the metamorphic Grimsel Granite and the sedimentary Mont Terri Opalinus Clay. The results show that Mode I cracks in anisotropic rocks tend to kink towards the foliation or bedding planes that are weaker in strength. The experiment data for kink angle and apparent fracture toughness are compared to the predictions of three well-known crack growth criteria: the maximum tangential stress (MTS), the maximum energy release rate (MERR), and the minimum (maximum in anisotropic materials) strain energy density (MSED). All these criteria overestimate the kink angle, while underestimating the apparent fracture toughness. The MTS yields predictions that are closest to the experiment data, while the MSED predictions are the furthest. We also show that the inclusion of the T-stress into the MTS criterion improves the predictions of the fracture growth. This indicates that the T-stress can play a significant role in the Mode I fracture growth of anisotropic rocks.